Efektivitas Program Kartu Identitas Anak (KIA) Dalam Meningkatkan Pelayanan Publik Bagi Anak di Kota Semarang - Devauli, Bella; Nur Cahyanto, Herbasuki; Marom, Aufarul (Journal of Public Policy and Management Review, 2024)
The government has the responsibility to protect its people from everything. This has prompted the government to issue regulations on children, such as the Ministry of Home Affairs Regulation No. 2/2016 on Child Identity Cards, which aims to improve data collection, protection, and the constitutional rights of citizens. Semarang is one of the cities that implemented KIA, but it has not been able to reach all children. This research uses descriptive qualitative method, and the research location is Semarang City Population and Civil Registration Office. This study aims to analyze the effectiveness of the implementation of the KIA program and the factors that hinder the effectiveness of KIA implementation by combining 3 expert theories according to Makmur (2011), Duncan (2009), and Budiani (2017), namely: accuracy of objectives, accuracy of targets, adaptation and program socialization. In the indicator of accuracy of objectives, it is still not effective because the main objective of KIA, namely to increase the protection and fulfillment of children's constitutional rights as citizens and improve public services for children, is still considered less than optimal. The target accuracy indicator is still not effective because the achievement of the KIA ownership target in 2023 is still far from the target that has been set. In the adaptation indicator, the Population and Civil Registration Office of Semarang City has also carried out various strategies and collaborations to increase KIA ownership. The socialization of the program is said to be.